Learning motivation and class management contribution to learning outcomes of vocational education student - Suryani, Karmila; ., Ambiyar; ., Khairudin (International Journal of Engineering and Technology, 2019)
This study aims to analyze the magnitude of the influence of learning motivation and classroom management of the learning outcomes of vocational education students in Padang City. This type of research is descriptive correlational research. In this study the researchers distributed questionnaires to the sample class. The sampling technique is simple random sampling, which is taking samples from all members of the population randomly by collecting the test scores of class X II students of Computer and Network Engineering (TKJ) , the Vocational Middle School (SMK) in Padang City then performing a normality test there were 33 people in the XII TKJ SMK Muhammadiyah 1 Padang , homogeneity and similarity in average . Learning outcomes data obtained from the learning outcomes test is the value of the test questions that have been tested in other SMKs, this data is a reflection of the learning outcomes of students in Productive subjects. While the data on learning motivation and classroom management were collected through questionnaires using the Likert scale which had been tested for validity and reliability. Then the data were analyzed using statistical methods with the help of SPSS version 17 for analysis of correlation and regression. The results of data analysis show: (1) Motivation to learn contributes to learning outcomes by 67.24%, (2) Management of classes contributes to learning outcomes of 3.496% and (3) Motivation for learning and classroom management contribute together to the learning outcomes of 0.61%. Based on the results of the study, it can be concluded that learning motivation and classroom management contribute to student learning outcomes.Â Â